Numerical validation of the “critical wave groups” method for the probabilistic assessment of ship stability in irregular beam seas - Παπαγεωργίου, Γεώργιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Μελέτης Πλοίου και Θαλάσσιων Μεταφορών, 2017)
This thesis deals with the numerical validation of the “critical wave groups” method that was developed by Themelis & Spyrou (2007) for the probabilistic assessment of ship stability. The method approximates the probability of ship instability by the probability of encountering any wave group that could have provoked the instability. In the original formulation of the method, ship dynamic stability was tested against regular waveforms. In this work, the focus is set on the study of ship roll motions in irregular beam seas and a reformulation of the “critical wave groups” method is attempted by employing realistic wave group excitations. The latter derive from the method of Anastopoulos et al. (2016) and represent the “most expected” wave groups of a sea state. The probability of exceeding a number of different heeling angles is computed and the results are compared to those obtained when assuming regular wave groups, as in the original methodology. Comparisons with the distribution of roll angles calculated by direct Monte Carlo simulations of ship motion are also included. The results indicate that consideration of irregular wave groups leads to more accurate results for a range of small to medium heeling angles. Possible ways to improve the method are proposed and its practicality for the assessment of ship stability is discussed.